2019
DOI: 10.1002/vnl.21713
|View full text |Cite
|
Sign up to set email alerts
|

Multiarm hyperbranched polyester‐b‐Poly(ε‐caprolactone):Plasticization effect and migration resistance for PVC

Abstract: A series of multiarm structure hyperbranched polyester‐b‐poly(ε‐caprolactone) (HEPCLs) with different lengths of poly(ε‐caprolactone) (PCL) segments (s = 3, 6, 7, 8) were synthesized. Hyperbranched polyester (HE) was synthesized from glycidol and succinic anhydride and used as a macromolecular polymerization initiator for ε‐caprolactone. The HEPCLs were used as polyvinyl chloride (PVC) plasticizers and the mechanical properties, thermal properties, morphology, and migration stabilities of PVC films were explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Similar studies were carried out by Li et al [ 50 ] The new plasticizer was synthesized through a reaction of glycidyl and succinic anhydride. In the second step, the obtained hyperbranched polyester acted as an initiator in reactions with ɛ-caprolactone via ring-opening polymerization.…”
Section: New Primary Plasticizersmentioning
confidence: 71%
See 1 more Smart Citation
“…Similar studies were carried out by Li et al [ 50 ] The new plasticizer was synthesized through a reaction of glycidyl and succinic anhydride. In the second step, the obtained hyperbranched polyester acted as an initiator in reactions with ɛ-caprolactone via ring-opening polymerization.…”
Section: New Primary Plasticizersmentioning
confidence: 71%
“…In comparison to their linear counterparts, hyperbranched plasticizers exhibit high terminal functional group concentrations and, therefore, are able to increase free volume in polymer matrices. On the other hand, a high molecular weight plasticizer is usually difficult to process, especially because of its higher viscosity [ 48 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of SPLA polymers caused an increase as expected due to the four flexible PCL arms in its structure, a slight increase is observed with the increase in arm length of the star polymer. Three‐dimensional molecular architecture has a significant influence on mechanical properties, and it was reported in the literature that branched PCL polymers gives better plasticizing effect than linear PCL and the increase of PCL segment in the material cause increments in mechanical properties 13,34,48,50 . Li et al investigated the effect of different CL segment lengths by synthesizing multiarmed hyperbranched polyester‐ b ‐PCL and found that it significantly improved the compatibility and plasticization efficiency of PVC 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Threedimensional molecular architecture has a significant influence on mechanical properties, and it was reported in the literature that branched PCL polymers gives better plasticizing effect than linear PCL and the increase of PCL segment in the material cause increments in mechanical properties. 13,34,48,50 Li et al investigated the effect of different CL segment lengths by synthesizing multiarmed hyperbranched polyester-b-PCL and found that it significantly improved the compatibility and plasticization efficiency of PVC. 50 As seen in Figure 4(b), a tremendous increase was observed when PDI was added to PLA/SPLA20 system especially in 90/10 blends, showing that the stronger interaction occurs between PLA and SPLA20 polymer in the presence of PDI.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation